Narative Review: Factors Influencing Medication Compliance of Hypertension Patients - Rizka Putri; Diana Rahmatillah; Kashif Khan (Indonesian Journal Publisher, 2026)
Hypertension is a chronic disease that requires long-term therapy to reduce the risk of cardiovascular complications, stroke, and kidney disorders. The success of antihypertensive therapy is largely determined by patient compliance in taking medication) (however, various reports indicate that compliance rates remain suboptimal. This narrative review aims to summarize recent evidence regarding factors influencing medication adherence among patients with hypertension. A systematic literature search was conducted in national and international journals published between 2020 and 2025, using predefined inclusion and exclusion criteria. The initial search identified 72 articles, of which 25 articles met the eligibility criteria and were included in the final thematic synthesis. The findings indicate that medication compliance is influenced by internal factors (knowledge, motivation, and self-efficacy) and external factors (family support, the role of health workers, perception of illness, and sociodemographic characteristics). Among these factors, treatment motivation and family support were consistently reported as the most dominant determinants of adherence. In conclusion, improving medication compliance in hypertensive patients requires a comprehensive approach that integrates continuous patient education, strengthening the role of health workers, and active family involvement in the treatment process.